(untitled) (Journal of Management and Educational Sciences, 2025)
As educational reforms emerge worldwide, the role of teachers in such change efforts is increasingly being monitored. Teachers’ capacity to make choices and implement actions to bring about change is often referred to as teacher agency. The need to examine teacher agency is increasingly recognized, particularly in contexts where new standardization and accountability plans reduce teachers’ professional autonomy while increasing demands on their work. Teacher agency is increasingly recognized as an important quality of teachers in making meaningful changes in their lives and professional environments, starting with classroom teaching. In recent years, there has been a significant increase in the number of publications on teacher agency. However, the emerging literature also reveals differences in conceptualizations and empirical findings related to teacher agency. It has been observed that teachers implement their professional actions differently in educational contexts and even among teachers within the same context. In this study, theses written in the field of teacher agency in Turkey were examined. In this context, the aim of this research is to examine postgraduate theses written on teacher agency in the context of various variables.